2017
DOI: 10.1101/212712
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Widespread dynamic and pleiotropic expression of the melanocortin-1-receptor (MC1R) system is conserved across chick, mouse and human embryonic development

Abstract: Background: MC1R, a G-protein coupled receptor with high affinity for alpha-melanocyte

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
1
0
1
Order By: Relevance
“…5J). Previous studies reported that MC1R is expressed in CNS neurons in late gestation [44] and neuron cultures prepared from C57BL/6J embryos [18]. To characterize αSyn toxicity and the effect of MC1R in primary cortical neurons, cell preparations from WT and MC1R e/e mice were transduced with BiFC αSyn AAV or control venus AAV at day in vitro (DIV)3 and treated with the MC1R agonist NDP-MSH 2 days later.…”
Section: Mc1r Activation Alleviates αSyn Oligomerization and Neurotoxicity By Activating Nrf2 In Vitromentioning
confidence: 99%
“…5J). Previous studies reported that MC1R is expressed in CNS neurons in late gestation [44] and neuron cultures prepared from C57BL/6J embryos [18]. To characterize αSyn toxicity and the effect of MC1R in primary cortical neurons, cell preparations from WT and MC1R e/e mice were transduced with BiFC αSyn AAV or control venus AAV at day in vitro (DIV)3 and treated with the MC1R agonist NDP-MSH 2 days later.…”
Section: Mc1r Activation Alleviates αSyn Oligomerization and Neurotoxicity By Activating Nrf2 In Vitromentioning
confidence: 99%
“…Однако экспрессия этого гена в макрофагах, лимфоцитах и других тканях [9] дает основания для рассмотрения роли МКР1-опосредованного пути как защитного механизма клеток и, в частности, нейронов мозга, который, очевидно реализуется при различных воспалительных процессах [10]. Вместе с тем экспрессия Мкр1 выявлена у эмбрионов различных видов позвоночных, что может свидетельствовать о плейотропном эффекте гена Мкр1 для нормального эмбрионального развития организма, что, по-видимому, эволюционно является весьма консервативным свойством [11].…”
Section: Introductionunclassified